Unseen Cinema: The Devil's Plaything, American Surrealism - Shepard, David
Early American avant-garde cinema from 1894-1941. Edwin S. Porter and other early filmmakers used bizarre sets, fantastic costumes, and magic lantern tricks to illuminate their fantasy films. American parody supplied Douglas Fairbanks with enough unusual material to produce the truly surreal When the Clouds Roll By (1919). The expressionistic Cabinet of Dr. Calagari (1919) influenced American sensibilities throughout the 1920s as seen in Beggar of Horseback (1925), The Life and Death of 9413-A Hollywood Extra (1927) and The Telltale Heart (1928). The emphasis shifted when amateurs J.S. Watson, Jr., Joseph Cornell, and Orson Welles crafted a unique variety of American surrealism on film unfettered by European concerns. 17 FILMS: Jack and the Beanstalk (1902)—Edwin S. Porter Dream of a Rarebit Fiend (1906)—Edwin S. Porter The Thieving Hand (1907)—creator unknown, Vitagraph Impossible Convicts (1905)—G.W. "Billy" Bitzer When the Clouds Roll By (1919)—Douglas Fairbanks & Victor Fleming (excerpt) Beggar on Horseback (1925)—James Cruze (excerpt) The Fall of the House of Usher (1926-27)—J.S. Watson, Jr. & Melville Webber The Life and Death of 9413: A Hollywood Extra (1927)— Robert Florey & Slavko Vorkapich The Love of Zero (1928)—Robert Florey & William Cameron Menzies The Telltale Heart (1928)—Charles Klein Tomatos Another Day (1930/1933)—J.S. Watson, Jr. & Alec Wilder The Hearts of Age (1934)— William Vance & Orson Welles Unreal News Reels (c. 1926)—Weiss Artclass Comedies (excerpt) The Children’s Jury (c. 1938)—attributed Joseph Cornell Thimble Theater (c. 1938)—Joseph Cornell Carousel: Animal Opera (c. 1938)—Joseph Cornell Jack’s Dream (c. 1938)—Joseph Cornell